Study of thrombolytic and anti-arthritic activities of flacourtia jangomas fruit - Tabassum, Nuzhat (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2023.